Is it justifiable to move the grade-1 ki67 index cut-off from 3% to 5% for pancreatic neuroendocrine tumors as has been proposed? The cases that fall to 3-5% category have clinicopathologic characteristics closer to those > 5% - Reid, Michelle; Balcı, Serdar; Bağcı, Pelin; Saka, Burcu; Pehlivanoğlu, Burçin; Erbarut Seven, İpek; Baştürk, Olca; Adsay, N. Volkan (Nature Publishing Group, 2020)
Background: Grading of linear parameters into meaningful (clinically relevant) clusters is a well-known challenge. Recently several groupshave proposed to change the Ki67 index cut-off for grade 1 (G1) category for PanNETs from < 3% to < 5%. This proposal presupposes thatthe cases with Ki67 index of 3-5% are NOT clinically different than the 0-3% group and thus can be lumped together with the current G1 (0-3% cases), instead of their current home in the G2 category (> 3%).
Keywords: Pancreatic Neuroendocrine; Clinicopathologic; Ki67 Index